Model Pembelajaran Tebak Kata Menggunakan Software Crossword Dalam Pengajaran Mufradat - Wiza, Rahmi (Institut Agama Islam Negeri (IAIN) Curup, 2018)
One of the constraints of students in learning Arabic is the lack of vocabulary. Students who have vocabulary memorization will be faster in learning Arabic lessons. One model of learning in teaching vocabulary is to use the word guessing model. The media used in studying mufradat/vocabulary should be easy, interesting and efficient to use. Educators are asked to be creative in presenting the media used by students. Crossword software is an application that can be used in making vocabulary learning media. This application can help educators in making crossword puzzles and guess words automatically, so the making of media for vocabulary teaching does not take too long and think hard because it is made manually. This application can automatically compile words that match the questions and answers provided by educators. Cross-sectional media or guess words, not only can be used when Arabic lessons take place in class but can be done independently by students. For educators making variations in presenting the form of questions is something that must be considered, so that students become interested and feel happy to use this media.